A conserved HOTAIRM1-HOXA1 regulatory axis contributes early to neuronal differentiation - Dana Segal; Samy Coulombe; Jasper Sim; Josée Dostie (RNA Biology)
HOTAIRM1 is unlike most long non-coding RNAs in that its sequence is highly conserved across mammals. Such evolutionary conservation points to it having a role in key cellular processes. We previously reported that HOTAIRM1 is required to curb premature activation of downstream HOXA genes in a cell model recapitulating their sequential induction during development. We found that it regulates 3’ HOXA gene expression by a mechanism involving epigenetic and three-dimensional chromatin changes. Here we show that HOTAIRM1 participates in proper progression through the early stages of neuronal differentiation. We found that it can associate with the HOXA1 transcription factor and contributes to its downstream transcriptional program. Particularly, HOTAIRM1 affects the NANOG/POU5F1/SOX2 core pluripotency network maintaining an undifferentiated cell state. HOXA1 depletion similarly perturbed expression of these pluripotent factors, suggesting that HOTAIRM1 is a modulator of this transcription factor pathway. Also, given that binding of HOTAIRM1 to HOXA1 was observed in different cell types and species, our results point to this ribonucleoprotein complex as an integral part of a conserved HOTAIRM1-HOXA1 regulatory axis modulating the transition from a pluripotent to a differentiated neuronal state.